Fungal Sepsis in a Tertiary Neonatal Intensive Care Unit: A Cross-sectional Study - Kheya Ghosh Uttam; Purbasha Gupta; Sumon Poddar (Pediatric Infectious Disease)
Aim and background: Fungal infections have emerged as a significant cause of late-onset neonatal sepsis in the last two decades. Epidemiological data on fungal sepsis in neonates especially in the Indian population is scarce. This study aims to determine the epidemiological trend of neonatal fungal infection, the organisms, and their susceptibility pattern to the different antifungal agents and additionally to look for the various risk factors, clinical features, and laboratory manifestation of fungal sepsis in neonates. Materials and methods: This is a retrospective observational study conducted in the NICU of a pediatric tertiary care hospital in Kolkata from January 2018 to December 2020. All the neonates who had a blood culture positive for Candida were included in the study. The type of organisms and susceptibility pattern to antifungal agents were noted. The clinical details like the age and sex of the neonate, gestational age at delivery, birth weight, and other predisposing risk factors like intravascular devices, mechanical ventilation, parenteral nutrition, and the laboratory parameters were noted. Results: Seventy-nine neonates whose blood culture was positive for Candida species were included in the study. Out of them, 65% were preterm (n = 52) and 67% were low birth weight (LBW). The chief presenting feature of the neonates was abdominal distension (39%), lethargy, refusal to feed (34%), respiratory distress (36%), convulsion (20%), and low-grade fever (5%). Sixty-one percent of the neonates required mechanical ventilation. Seventy-six percent (n = 60) of the babies were receiving parenteral nutrition with either peripheral or central line on the day blood culture was sent. Sixty-seven percent (n = 53) of the patients were diagnosed with fungal sepsis based on first blood culture on the day of admission (group I), whereas 33% (n = 26) were diagnosed after a few days of admission to NICU (group II). All the babies in group I were outborn and the average age of referral was day 7. In group II, 61.5% (n = 16) were outborn and 38.5% (n = 10) were inborn and the average age of positive fungal culture was day 12. Among the isolates, 43% were Candida pelliculosa, 31% were Candida parapsilosis, 8% were Candida famata, 7% were Candida tropicalis, 2.9% were Candida krusei, 5.7% Candida guilliermondii, and only 2.3% were Candida albicans. As per the culture sensitivity report, 13% (n = 10) of the Candida species were resistant to antifungal agent fluconazole but 100% were sensitive to voriconazole; 11% (n = 9) resistant to amphotericin B; 2.5% (n = 2) were intermediate sensitive, and 5% (n = 4) resistant to both caspofungin and micafungin. The general mortality rate was 32.9% (n = 26). The babies in group I had a higher mortality rate (37.7%) compared with the babies in group II (23%). Infection with C. tropicalis has the highest mortality (42.3%), followed by C. parapsilosis (30.7%) and C. pelliculosa (27%). Interpretation: Our study revealed that fungal infection in neonates is mostly due to non-albicansCandida species (97.3%), C. pelliculosa was found to be the commonest organism accounting for 43% of infection. Infection with C. tropicalis was associated with maximum mortality. Thirteen percent of the Candida species were resistant to the drug fluconazole, 11% were resistant to amphotericin B, 5% were resistant to caspofungin and micafungin, whereas all of the organisms were sensitive to voriconazole. Preterm, LBW, need for mechanical ventilation, parenteral nutrition, and broad-spectrum antibiotics play a significant role in fungal sepsis-related morbidity and mortality.